2021
DOI: 10.3390/molecules26134045
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Templated Fluorescent Silver Nanoclusters Inhibit Bacterial Growth While Being Non-Toxic to Mammalian Cells

Abstract: Silver has a long history of antibacterial effectiveness. The combination of atomically precise metal nanoclusters with the field of nucleic acid nanotechnology has given rise to DNA-templated silver nanoclusters (DNA-AgNCs) which can be engineered with reproducible and unique fluorescent properties and antibacterial activity. Furthermore, cytosine-rich single-stranded DNA oligonucleotides designed to fold into hairpin structures improve the stability of AgNCs and additionally modulate their antibacterial prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 47 publications
1
55
0
Order By: Relevance
“…Our previously published data suggested that the formation of alternative DNA structures via strong silver mediated C-Ag-C base paring results in heterogeneity of DNA-AgNC populations [6]. HL nucleic acid structures appear to improve the results by forming a homogeneous, both structurally and optically, population of AgNCs [23]. HL consists of a base-paired stem and a loop sequence with unpaired nucleotide bases (Figure 1A) and represent a key building block of many folded RNA secondary structures found in nature, including ribozymes and messenger-RNA [24].…”
Section: Design Of the Hairpin-loop Agnc Dna Templatementioning
confidence: 96%
See 4 more Smart Citations
“…Our previously published data suggested that the formation of alternative DNA structures via strong silver mediated C-Ag-C base paring results in heterogeneity of DNA-AgNC populations [6]. HL nucleic acid structures appear to improve the results by forming a homogeneous, both structurally and optically, population of AgNCs [23]. HL consists of a base-paired stem and a loop sequence with unpaired nucleotide bases (Figure 1A) and represent a key building block of many folded RNA secondary structures found in nature, including ribozymes and messenger-RNA [24].…”
Section: Design Of the Hairpin-loop Agnc Dna Templatementioning
confidence: 96%
“…AgNCs are highly susceptible to oxidation with dramatic changes in optical properties of the nanoclusters [6]. A closed geometry of DNA/RNA templates results in an improved stability of AgNCs against oxidative species present in solution, including dissolved oxygen [7,23]. Looped templates used in the current study, therefore, provide additional advantages of increased AgNCs stability.…”
Section: Design Of the Hairpin-loop Agnc Dna Templatementioning
confidence: 97%
See 3 more Smart Citations